Auditoría de gestión a los procesos de contratación pública del hospital del niño Dr. Francisco de Icaza Bustamante ciudad Guayaquileño 2023 - Mera Gómez, María Gabriela (2025)
This research aims to evaluate the impact of management auditing on the public procurement processes at the Hospital del Niño Francisco de Icaza Bustamante during the year 2023. A mixed-methods approach was employed, combining qualitative and quantitative perspectives, and utilizing inductive, deductive, historical-logical, and descriptive methods. Through comprehensive data collection and analysis, critical factors affecting the efficiency and transparency of public resource management were identified. Although the hospital operates under a broad and detailed regulatory framework governing public procurement, inconsistencies in its practical application were observed, largely due to the complexity and continuous updates of laws and regulations, which demand ongoing specialized training for the personnel involved. The management audit revealed levels of non-compliance in several key stages of the procurement process. Finally, the preparation of the management report generated valuable tools for designing and implementing strategies aimed at significantly improving the execution of public procurement processes within the institution.